Remediation for surgical trainees: recommendations from a narrative review. Issue 6 (3rd February 2021) - To, Henry; Cargill, Ashleigh; Tobin, Stephen; Nestel, Debra
Abstract : Remediation involves formalized support for surgical trainees with significant underperformance to return to expected standards. We have reviewed current published literature to understand the evidence for remediation of surgical trainees to inform practice and justify investment of resources. If performed in a programmatic framework, it is a complex but often successful approach to return surgical trainees to their expected standard using system and process level changes. Abstract: Background: Remediation involves formalized support for surgical trainees with significant underperformance to return to expected standards. There is a need to understand current evidence of remediation for surgical trainees to inform practice and justify investment of resources. Methods: Following the principles of a systematic review, we conducted a narrative analysis to make recommendations for remediation of underperforming surgical trainees. Results: From a review of 55 articles on remediation of trainees in medical and surgical sub‐specialities, we have identified system and process level recommendations. Remediation is reported as long‐term, complex and resource‐intensive. Establishing a defined and standardized remediation framework enables co‐ordination of multi‐modal interventions. System level recommendations aim to consolidate protocols via developing better assessment, intervention and re‐evaluation modalities whilst also strengthening support to supervisors conducting the remediation. Process level recommendations should be tailored for the specific needs of each trainee, aiming to be proactive with interventions within a programmatic framework. Regular reassessment is required, and long‐term follow‐up shows that remediation efforts are often successful. Conclusion: While remediation within a programmatic framework is complex, it is often a successful approach to return surgical trainees to their expected standard. Future directions involve applying learning theories, encouraging research methods and to develop integrated collaborate protocols and support to synergize efforts.